2015
DOI: 10.1007/s13197-015-1856-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caponization on the production performance, slaughter yield and fatty acid profile of muscles of Greenleg Partridge cocks

Abstract: The study was conducted to assess the effects of surgical caponisation on the production performance, share of respective elements of the carcass, basic chemical composition and fatty acid profile of muscles of Greenleg Partridge cocks. Two hundred twenty healthy day chicks were randomly distributed into two experimental groups (caponised and uncaponised). The birds were caponised at the age of 8 weeks old and slaughtered at 23 weeks of age. It was observed that capons tended to consume more feed. The studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 33 publications
12
20
0
2
Order By: Relevance
“…*The fatty acid composition is shown only in the capons, as there is no abdominal fat in cock carcass (Table 4). Previous studies (Kwiecień et al, 2015) demonstrated significantly higher fat contents in Zk capons than in cocks of this breed. Similarly, Sirri et al (2009) showed lower levels on adiposity of breast muscles in cocks, compared with capons.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…*The fatty acid composition is shown only in the capons, as there is no abdominal fat in cock carcass (Table 4). Previous studies (Kwiecień et al, 2015) demonstrated significantly higher fat contents in Zk capons than in cocks of this breed. Similarly, Sirri et al (2009) showed lower levels on adiposity of breast muscles in cocks, compared with capons.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, the fatty acid composition is also influenced by the breed and age at caponisation (Miguel et al, 2008;Sirri et al, 2009). The difference in the fatty acid composition between breeds may be related to the different fat content in muscles (Kwiecień et al, 2015). The meat of slow-growing chickens is nutritionally healthier, as it contains lower amounts of fat and has higher n-3 PUFA content (Sirri et al, 2011); therefore, it can be preferred by consumers seeking healthy, organic products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations